Strategy To Improve Family Card Administration Service In Purwosari Village, Purwosari District, Pasuruan Regency - Rossa Ilma Silfiah; Hambali; Nisaul Mufida (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Family Card is one of the important documents in population administration. Therefore, Family card services must have a certain quality in order to provide the best service to the community. The purpose of this research was to determine the quality of service and to determine the supporting factors in fulfilling the quality of family card services. In carrying out a satisfactory service, the Purwosari Sub-District Office, Purwosari district also applies strategies to improve the performance of the apparatus. This type of research is descriptive with a qualitative approach. The research process involves asking questions and procedures, collecting data from participants, analyzing inductively, interpreting the meaning of the data. From the research conducted, it shows that the quality of Family Card services at the Purwosari sub-district, Purwosari district viewed from the dimensions of reliability, physical evidence (tangibles), responsiveness, assurance, and empathy is good, although there are not optimal. The strategy implemented is the core strategy includes the vision and mission, the consequence strategy includes reward and punishment, the customer strategy is also detailed in the Service Operational Standards, Public Service Standards and service announcements. The control strategy is the authority delegation from the Population and Civil Registration Office and the authority delegation to the Ombudsman as well as cultural strategies by implementing 5S they are Senyum (smile), Sapa (addressing), Salam (greetings), Sopan (courtesy), and Santun (manners) and morning assembly activities. In an effort to improve the quality of Family Card services, there are supporting factors that can affect service quality. The supporting factors in fulfilling the quality of Family Card services which include the behavior of the apparatus and the capabilities of the apparatus are also quite good.